The Effectiveness of media Instagram towards the students' vocabulary mastery - Muliana; Silvi Listia Dewi (Journal of English Education and Social Science, 2023)
This research aims to see whether the mean score of XI students of SMA Negeri 3 Bireuen who taught using Instagram media to master vocabulary in writing recount texts got a higher score than the mean score of students who used conventional methods. The methodology of this research was a quasi-experimental (nonequivalent control group) design. The instrument used in this research was an achievement test. The data was analyzed quantitatively using the SPSS Statistics Output, such as Normality Test, homogeny test, and Independent-Sample T-test. Using Instagram as media for the student's vocabulary mastery in writing recount text is effective. It can be seen from the average score of the control and experimental classes, where the average value of the control class is 47.65 while the average value of the experimental class is 77.94. That way, there is a difference between the two classes, where the experimental class taught using Instagram has a higher value than the control class taught using the convection method. From the data analysis, the result of the Independent Sample T-test is 0.000 < 0.05, so it can be concluded that there is a difference in the average student learning outcomes between the learning model that uses Instagram media and the conventional learning model. Thus, the research alternative hypotheses (Ha) are accepted, and the null hypotheses (Ho) are rejected. Then, the effectiveness of the media Instagram towards the students' vocabulary mastery in writing recount text is effective.